PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA GURU DI SEKOLAH MENENGAH KEJURUAN - Clara Ovie Wijaya; Dwi Yulianti; Herpratiwi Herpratiwi (Akademika : Jurnal Teknologi Pendidikan, 2023)
One thing that requires to be done in providing growth in educator standards, in the field of education is to improve the workforce's or teachers' performance. Any activity that applies responsibility or is helpful in the workplace qualifies as training. This training was expected to help teachers develop their hard and soft skills. Education and training are required for educators in vocational high schools to work better and become more competent. By using the Systematic Literature Review (SLR) method, the results of the study showed that the work of educators in schools has a significant effect on education and training.